Experimental Motion Analysis of Radially Rotating Beams Using High-Speed Camera and Motion Analyzer - K.H. Low; Michael W.S. Lau; K.K. Low (Shock and Vibration)
Although strain gauges can be attached to a system for vibration analysis, wires connected to the strain gauges may disturb the system and affect the accuracy of the strain measurement. As an alternative, this work presents the use of a high-speed camera combined with a motion analyzer to study the motion of rotating flexible beams. One end of the beam is rigidly connected to a motor, while the other end is free. White stickers placed on selected points on a given beam are the reference points in a digitization process. The modes of the vibrating beams can be filmed and analyzed. The vibration parameters, such as deflection and frequency, can be obtained by using a film motion analyzer. The results show that the beam does not behave in a clamped-free or a pinned-free fashion, but instead occurs at an intermediate boundary between these two classical conditions.